Lipopolysaccharide preconditioning reduces liver metastasis of Colon26 cells by enhancing antitumor activity of natural killer cells and natural killer T cells in murine liver. Issue 7 (31st December 2020) - Nishikawa, Makoto; Kinoshita, Manabu; Morimoto, Yuji; Ishikiriyama, Takuya; Nakashima, Masahiro; Nakashima, Hiroyuki; Ono, Takeshi; Seki, Shuhji; Moriya, Tomoyuki; Yamamoto, Junji; Kishi, Yoji
Abstract: Background and Aim: Lipopolysaccharide (LPS) preconditioning drastically augments bactericidal activity but reduces the host inflammatory response. Therefore, it may be beneficial to prevent postoperative infectious complications and mitigate host damage by surgical stress. Considering its clinical application, how LPS preconditioning influences the antitumor effect in the liver is an important issue. We then investigated the effect of LPS preconditioning on antitumor activity against Colon26 tumor cells in mice. Methods: Lipopolysaccharide preconditioning was induced in mice by the intraperitoneal injection of 5 μg/kg LPS for three consecutive days. Intraportal inoculation of Colon26 cells, which express luminescent protein called Nano‐lantern, was performed to evaluate the effect of LPS preconditioning on tumor liver metastasis. The antitumor activities of cytotoxic liver lymphocytes, especially natural killer (NK) cells and natural killer T (NKT) cells, against Colon26 cells were also examined in LPS preconditioned mice. Results: Lipopolysaccharide preconditioning remarkably prevented liver metastasis of Colon26 cells, as observed by IVIS imaging system, and prolonged survival after tumor inoculation. LPS preconditioning increased the proportions and number of liver NK cells and NKT cells and augmented their intracellular perforin and granzyme B expression, while reducing their intracellular expression of IFN‐γ. An in vitro antitumor cytotoxicity assay revealed that LPS preconditioning significantly augmented antitumor cytotoxicities of the liver NK cells and NKT cells, especially NKT cells, against Colon26 cells. Conclusions: Lipopolysaccharide preconditioning potently augmented antitumor cytotoxicity of liver NK cells and NKT cells, thereby improving mouse survival after intraportal inoculation of Colon26 tumor cells. It may be useful for perioperative care in oncological patients.